Tariffs and the Balance of Payments: Comment - Johnson, Harry G. (Quarterly Journal of Economics, 1958)
Tariffs and the Balance of Payments: Comment Get access Harry G. Johnson Harry G. Johnson University of Manchester Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 72, Issue 2, May 1958, Pages 301–302, https://doi.org/10.2307/1880604 Published: 01 May 1958